Transportation security. Volume 9, (Transportation Research Board, 2006)
TRB's National Cooperative Highway Research Program (NCHRP) Report 525: Surface Transportation Security and TRB's Transit Cooperative Research Program (TCRP) Report 86: Public Transportation Security series publications have jointly published Guidelines for Transportation Emergency Training Exercises. The report is Volume 9 in each series. The report is designed to assist transportation agencies in developing drills and exercises in alignment with the National Incident Management System. The report describes the process of emergency exercise development, implementation, and evaluation. In addition, the available literature and materials to support transportation agencies such as state departments of transportation, traffic management centers, and public transportation systems are described.
At head of title: Transit Cooperative Research Program and National Cooperative Highway Research Program.
Title from PDF title page (viewed July 24, 2007).
Keywords: Transportation -- Security measures -- United States.; Transportation -- United States -- Safety measures.; Transportation agencies -- United States -- Planning.; Transportation -- Planning.; Civil defense.; Emergency management.; elektronické knihy; electronic books